Legitimacy driven change at the World Anti-Doping Agency. Issue 2 (3rd April 2019) - Read, Daniel; Skinner, James; Lock, Daniel; Houlihan, Barrie
ABSTRACT: The effectiveness of the World Anti-Doping Agency as an international non-governmental organisation with a mission to regulate anti-doping policy has been challenged by doping scandals in sport. Historically, anti-doping policy development has been primarily reactive, determined by the need for dominant organisations to maintain power rather than to protect athletes. The purpose of this paper is to explore reactive anti-doping policy change from a multi-level legitimacy perspective. Using multi-level legitimacy theory and the concept of legitimacy challenges, it is argued that reactive policy change is motivated by a need to manage perceived organisational legitimacy. The recent exposure of systematic doping in Russia is used as an example to support this analysis. These findings are discussed in the context of current criticisms of anti-doping policy.